2015
DOI: 10.1002/pon.3793
|View full text |Cite
|
Sign up to set email alerts
|

Concealment of lung cancer diagnosis: prevalence and correlates

Abstract: Objective Lung cancer has a commonly-understood behavioral etiology. Thus, lung cancer patients are often blamed for their illness and may seek to avoid this blame by concealing their diagnosis from others. This study sought to determine the prevalence of concealment and identify demographic, clinical, and psychosocial correlates of concealment among lung cancer patients. Methods A sample of 117 lung cancer patients receiving chemotherapy for non-small cell or small cell lung cancer was recruited and complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 39 publications
0
28
1
Order By: Relevance
“…17 People with low self-esteem may be more likely to perceive others' reactions as rejection and consequently to feel more severe levels of stigma than people with high self-esteem. 21 In this study, responses were measured using 1 and 2 for answers of 'yes' and 'no', respectively. 19 Individuals who have a high level of coping self-efficacy may be more likely to effectively cope with receiving a cancer diagnosis and the negative reactions of other people than those with low level.…”
Section: Introductionmentioning
confidence: 99%
“…17 People with low self-esteem may be more likely to perceive others' reactions as rejection and consequently to feel more severe levels of stigma than people with high self-esteem. 21 In this study, responses were measured using 1 and 2 for answers of 'yes' and 'no', respectively. 19 Individuals who have a high level of coping self-efficacy may be more likely to effectively cope with receiving a cancer diagnosis and the negative reactions of other people than those with low level.…”
Section: Introductionmentioning
confidence: 99%
“…Perspective‐taking, that is, cognitive‐empathy, refers to the tendency to put oneself in the other's place and may be associated with self‐concealment behavior, as it often reflects a concern for others . Specifically, individuals characterized by greater perspective‐taking may display greater concealment behavior, as they imagine that their partners would respond with distress to their sharing of cancer‐related concerns.…”
Section: Introductionmentioning
confidence: 99%
“…16 Perspective-taking, that is, cognitive-empathy, 17 refers to the tendency to put oneself in the other's place 18 and may be associated with self-concealment behavior, as it often reflects a concern for others. 19 Specifically, individuals characterized by greater perspectivetaking may display greater concealment behavior, as they imagine that their partners would respond with distress to their sharing of cancerrelated concerns. On the other hand, one's greater perceived level of spousal support may be associated with a decrease in self-concealment behavior, as-conversely-the perception of partner responses as unsupportive has been associated with greater holding back from talking about cancer-related concerns and/or with avoidant coping.…”
mentioning
confidence: 99%
“…As in previous research, stigma was described as a reason why some patients may not seek care or support and why treatments and support might not be offered to lung cancer patients [1820]. Nihilism was repeatedly reported as a reason why clinicians may not offer treatment and why patients and carers themselves may not accept or seek treatment.…”
Section: Discussionmentioning
confidence: 85%
“…Research from North America has found stigma and shame about lung cancer, social isolation and smoking-related stigma to be associated with delay in seeking medical help by lung cancer patients [18, 19]. Other researchers have found that lung cancer patients who have more internalised shame about their cancer are more likely to conceal their diagnosis from their social network [20] and that the negative effects of stigma and shame on lung cancer patients distress and quality of life were mediated by cancer threat and social constraints [21]. Hence, stigma influences the patient experience of lung cancer and although objective studies of actual discrimination in cancer treatment are not evident, stigma seems likely to influence the care pathway.…”
Section: Introductionmentioning
confidence: 99%